filmov
tv
If roots of the equation(b-c)x²+(c-a)x+(a-b)=0 are equal, then prove that 2b=a+c|@Sk Wonder Kids.
Показать описание
If roots of the equation(b-c)x²+(c-a)x+(a-b)=0 are equal, then prove that 2b=a+c
If the roots of the equation (b-c)x^2+(c-a)x+(a-b)=0 are equal, then prove that 2b=a+c.
If the roots of the equation (b-c)x2+(c-a)x+a-b=0 are equal then prove that 2b = a+c
If the roots of the equation (a-b)x^2+(b-c)x+(c-a)=0 are equal prove that 2a=b+c
If the roots of the equation ax^2+cx+c=0 be in the ratio m:n,prove that,√m/n+√n/m+√c/a=0
If the roots of the equation (b-c)x2+(c-a)x+(a-b)=0 are equal, then prove that 2b=a+c.....
If the roots of (b-c)x2+(c-a)x+(a-b) = 0 are real and equal than which of the following is true:a)
If the roots of the equation (b−c)x2+(c−a)x+(a−b)=0 are equal, then prove that 2b=a+c
If roots of the equation(b-c)x²+(c-a)x+(a-b)=0 are equal, then prove that 2b=a+c|@Sk Wonder Kids.
AS 2025 Pure Maths Year 12 1st Term Review/Revision 20 minute Video Cover Discriminate, Binomial Cal
If the roots of the equation (b-c) x^2+(c-a) x+(a-b)=0 are equal, then prove that 2 b=a+c. W
Q24 If the roots of the equation (a-b)x²+(b-c)x+(c-a)=0 are equal then prove that 2a=b+c
The roots of the equation` (b-c) x^2 + (c-a)x+ (a-b) = 0`
If the roots of the equation (b-c) x^2+(c-a) x+(a-b) =0 are equal, then prove that 2b=a+c?
7. If a,b,c rational and a + b + c=0, show roots of (b+c–a)x² + (c+a–b)x +(a+b+c) = 0 are rational....
If a, b are the roots of x^2+px+1=0 and c, d are the roots of x^2+qx+1=0, the value of E=(a-c)(b-c)
If one of the roots of the equation then `a(b-c) x^2 + b(c-a) x + c (a-b) = 0` is what is th...
If the roots of the equation `(b-c)x^2+(c-a)x+(a-b)=0` are equal then `a,b,c` will be in
If `a+b+c=0, a,b,c in Q` then roots of the equation `(b+c-a) x ^(2) + (c+a-c) =0` are:
If \( a, b, c \in Q \), then roots of the equation \( (b+c-2 a) x^{...
6. Prove that if eq x² + bx +ca =0 and x² + cx +ab=0 have common root other roots satisfy x²+ax+bc=0...
If the roots of the equation (a-b)x^2 + (b-c)x + (c-a) = 0 are equal, then prove that 2a = b + c.
6. Show that roots of equation (a²–bc)x² + 2(b²–ca)x + (c²–ab) = 0 equal, if b=0 or a³+b³+c³–3abc=0....
If the roots of the quadratic equation (a-b)x² + (b-c)x + (c-a) = 0 are equal, prove that 2a = b+c.
If coefficients of the equation `ax^2 + bx + c = 0` , `a!=0` are real and roots of the equatio...
Комментарии